Phosphorus cardanol: chemical characterization and thermal stability - Rios, Maria Alexsandra de Sousa; Batista, F S. C. L.; Sales, F A. M.; Mazzetto, S E (Scientia Plena, 2016)
Due to the wide use of the cardanol to develop new additives, this study presents the chemical characterization of phosphorus cardanol using FTIR and Thermoanalytical techniques (TG / DSC / DTA), and the evaluation of the antioxidant potentiality of compound when added to a lubricating oil. In this paper, the authors also included the thermal study of phosphorus cardanol by heating in an oven, monitoring changes in FTIR. According to results, the phosphorus cardanol showed good thermal stability when compared with other compounds of the same class "phosphate esters" and showed no changes before and after heating at 120 ° C, under air atmosphere. Thus, the phosphorus compound derived from cardanol has potential application as additive for lubricating oils and petrochemicals of the same segment.